Mathematics Learning Experiment On Guided Inquiry Method And Open-Ended Method Viewed From Student's Critical Thinking Ability In Grade VII Of SMP N 1 Surakarta - Adiningsih, Sri; , Dr. Sumardi, M.Si (2013)
This research paper aims to know (1) the difference learning achievement between Guided Inquiry method and Open-Ended method in mathematics learning on the subject of Set, (2) the difference learning achievement viewed from student's critical thinking ability in mathematics learning on the subject of Set, (3) the interaction between Guided Inquiry method and student's critical thinking ability in mathematics learning against learning achievement learning on the subject of Set. Population of the research is all of students in grade VII of SMP N 1 Surakarta academic year 2012/2013 consist of 8 classes. The research sample is taken two classes, i.e. grade VIIG consist of 26 students be experiment class using Guided Inquiry learning and grade VIIH consist of 24 students be control class using Open-Ended learning. Type of research is experimental research with methods of collecting data using test, questionnaire and documentation. Prerequisites test this research using normality test and homogenity test. In this research use Two Way Analysis of Variance. The result of hyphotesis testing using α=5% it show that (1) Fobs=0,013 < Ftable=4,064 so H0 accepted, it means there isn't difference of learning methods to mathematics achievement on the subject of Set, (2) Fobs=5,008 > Ftable=3,214 so H0 rejected, it means there is difference of student's critical thinking to mathematics achievement on the subject of Set, (3) Fobs=0,107 < Ftable=3,214 so H0 accepted, it means there aren't interaction between learning methods and student's critical thinking to mathematics achievement on the subject of Set.